Regeneration Status and Carbon Accumulation Potential in Community Managed Sal (Shorea robusta) Forests of Far-Western Terai Region, Nepal - Joshi, Rajeev; Pangeni, Mandip; Neupane, Suman Shree; Yadav, Nagendra Prasad (European Journal of Ecology, 2021)
Regeneration patterns of species population can address climate change by adaptive evolution or by migrating association to survival in their favorable climate and finally decide the particular forest future. This research examined the status of regeneration and carbon sequestration potential in tropical Sal (Shorea robusta) forest of Kanchanpur district, Nepal. For the study, a total of 63 concentric sample plots were investigated by using systematic sampling with 0.5% sampling intensity. Regeneration status of forest was estimated by calculating the density of each species in each developmental phase. The above-ground carbon stock of trees species were estimated using allometric equations. The studied forests had good regeneration status and Shorea robusta was the dominant species in terms of regeneration and carbon stock. Ramnagar community forest had greater number of seedling, sapling and tree than that of the Ganesh community forest. Reverse J-shaped population curves were recorded at both the study sites. This study provided information about the regeneration status, structure, composition and carbon sequestration potential of tree species which is very necessary for conservation and sustainable management of community forests. Studies indicate that community management has increased the carbon stock of forests and also has promoted the productivity of forests by altering the structure and composition of the community forests.